Application of CAD/CAM technology for surgical treatment of condylar head fractures: A preliminary study - Tetiana Pavlychuk; Denis Chernogorskyi; Yurii Chepurnyi; Andreas Neff; Andrii Kopchak (Elsevier, 2020)
Objectives: The aim of the present study was to improve the accuracy and reliability of ORIF in patients with condylar head fractures (CHFs) by developing a design for patient specific fixators, navigation and repositioning guides, as well as the algorithms of their clinical application. Materials and methods: 14 patients with 16 CHFs were treated by ORIF with the use of CAD/CAM technology. After virtual reduction of the bony fragments, the appropriate length and diameter of the screws was chosen. In biomechanically unfavorable cases (type p) patient specific reinforcement plates were used together with the positional screws for reinforcement of the bone-fixator system. And in cases of severely comminuted fractures patient specific 3-D plate was applied. Results: The CT data, obtained immediately after the operation revealed the good anatomical reduction. Any deviations of the small fragments noted were near 1 mm in all cases. Postoperative clinical examination at 3 months follow up showed good occlusion and mouth opening not less than 3 cm in all patients. The lateral and anterior mobility of the mandible was restored with small limitations of protrusive mobility in 1 case. All the patients were satisfied with the outcomes. Conclusions: The application of the CAD/CAM technologies and the new design of the surgical guides and patient specific reinforcement plates for CHFs helps to improve the accuracy and quality of fragments reduction and stability of fixation with minimal risks of intraoperative complications. Clinical relevance: CAD/CAM technologies improve the clinical effectiveness of treatment patients with the CHFs.